TA`TSIIRU TA’LIIMU AL-LUGHAH AL-ARABIYYAH ‘LAA THALAQAH HIFDZIL QUR’AN LITHULLAABI AS-SHAFI AS-TSANII ‘ASYARA MINAL MADRASATI ‘ALIYAH CAHAYA QUR’AN CIBUNGBULANG BOGOR - Fitri Maelani; Asriani; Muh Abrar (Program Studi Pendidikan Bahasa Arab, 2022)
This research provides benefits to Arabic language teachers in helping to provide an easy educational motivation for students to master the Qur'an and memorize it through learning the Arabic language. That the author of this research be able to provide benefits in the application and application of mastering the Arabic language in memorizing the Qur’an. It can be a positive contribution and as a material consideration, especially for the educational institutions of the High School Jehai Qur'an Jbunbulang Bogor in improving the learning of the Arabic language towards the fluency of memorizing the Qur'an. The researchers would like to conduct further research on the comparison between the application of learning the Arabic language, especially in speaking skills, with the non-application of learning the Arabic language, especially in speaking skills, to the fluency of memorizing the Qur’an in this Institute of Tahfuz Al-Qur’an. Based on the results of the above research, learning the Arabic language has a great impact on the fluency of memorizing the Qur’an, especially for students who have mastered the ability to speak Arabic. Therefore, it is hoped that in the future this ability to speak will become a second priority in addition to memorizing the Qur'an, in order to make it easier for students to memorize the Qur'an